Transcatheter Closure of Atrial Septal Defect and Balloon Pulmonary Valvuloplasty with Inoue Balloon in Adult Patients. - Adhikari, Chandra Mani; Acharya, Kiran; Bogati, Amrit; Acharya, Anjana; Prajapati, Dipanker (Nepalese Heart Journal, 2021)
Secundum type atrial septal defect combined with pulmonic stenosis is a relatively uncommon condition in adult patients. When occurred separately they can be treated with transcatheter intervention. When they occur together ideal treatment option is not clear. We report a case of combined percutaneous pulmonary valvuloplasty done with the Inoue balloon and transcatheter atrial septal defect closure in an adult patient.